Potensi Kesulitan-Kesulitan Yang Dihadapi Siswa SMK Saat Menyelesaikan Masalah Materi Sistem Persamaan Linear Dua Variabel: Studi Eksploratif - Aprianti, Desi; Nugroho, Purna Bayu; Meilasari, Venty (International Journal of Progressive Mathematics Education, 2022)
This research is aim to find out the difficulties of concept and principle experienced by students in solving story problems of a system of linear equations two variables class x in SMK Muhammadiyah Kotabumi and the factors that cause students to experience these difficulties. The method used in this study is a descriptive method in the form of a case study. The subjects used in this study were several students of class x. The instrument used was a written test in the form of an essay. From the data analysis,it is known that the difficulties and the factors causing the difficulties experienced by student. Diifficulty assuming variable terms, difficulty converting story problems into mathematical sentences, difficulty performing operations with elimination and substitusion methods, difficulty operating addition and subtraction, difficulty converting variable replacement values into interrogative sentences. Lack of mastery of SPLDV material, lack of accuracy when working on question, and do not master the concepts and principles of SPLDV Keywords :